Commonality of Multidrug-Resistant Klebsiella pneumoniae ST348 Isolates in Horses and Humans in Portugal - Trigo da Roza, Filipa; Couto, Natacha; Carneiro, Carla; Cunha, Eva; Rosa, Teresa; Magalhães, Mariana; Tavares, Luís; Novais, Ângela; Peixe, Luísa; Rossen, John W.; Lamas, Luís P.; Oliveira, Manuela (Frontiers in Microbiology, 2019)
Multidrug-resistant (MDR) Klebsiella pneumoniae is considered as a major global concern by the World Health Organization. Evidence is growing on the importance of circulation of MDR bacterial populations between animals and humans. Horses have been shown to carry commensal isolates of this bacterial species and can act as human MDR bacteria reservoirs. In this study, we characterized an extended-spectrum β-lactamase (ESBL)-producing K. pneumoniae sequence type (ST) 348 isolate from a horse, an ST for the first time reported in an animal, using next-generation sequencing. We compared it with six other MDR K. pneumoniae ST348 human isolates previously identified in health-care facilities in Portugal using a core genome multi-locus sequence typing approach to establish an epidemiological link. The horse isolate was resistant to most of the antimicrobials tested, including 3rd generation cephalosporins, fluoroquinolones and aminoglycosides, and presented several antimicrobial resistance genes, including blaESBL. Twenty-one allele differences were found between the horse isolate and the most similar human isolate, suggesting a common ancestor or an epidemiological link. Other similarities were observed regarding the content on antimicrobial resistance genes, plasmid incompatibility groups, and capsular and somatic antigens. This study illustrates the relevance of the dissemination of MDR strains, and suggests that identification of these types of bacterial strains in both human and veterinary settings is of significant relevance in order to understand and implement combined control strategies for MDR bacteria in animals and humans.